Improving Understanding of 1-Dimensional Kinematics Concepts through Motion Diagram Approach - Asmarani Hafid; Hartati; Zainuddin; Andi Ardani Japeri (Universal Education, 2025)
Students' understanding of kinematics concepts still tends to be low because they have difficulty understanding concepts in various representations. This quantitative study investigates the effectiveness of the motion diagram approach in teaching one-dimensional kinematics through a pretest-posttest control group design. The experimental class utilized motion diagrams, while the control class was taught using conventional methods over a five-week period. The research was conducted at one of the public high schools in Makassar City. The experimental and control classes consisted of 36 students. Students' understanding was assessed using a validated set of 12 multiple-choice questions, with data analyzed through descriptive statistics and independent sample t-tests to evaluate differences in learning outcomes. Results indicated that the experimental class exhibited significantly more improvement in conceptual understanding than the control class, suggesting that motion diagrams enhance students' grasp of kinematic principles. The findings support integrating multi-representational learning strategies, facilitating students' active engagement and knowledge construction. The motion diagram approach effectively reduces cognitive load and promotes deeper understanding by visually representing motion and encouraging students to translate this information into tables, graphs, and equations. Additionally, the study highlights the importance of combining visual and verbal representations, which aligns with Dual Coding theory, enhancing retention and motivation. Overall, the research underscores the potential of innovative teaching methods, such as motion diagrams, to improve educational outcomes in physics, thereby enriching the learning experience and fostering a more profound comprehension of scientific concepts among students. In the future, similar experiments could be applied in broader contexts or in other subjects of physics, as well as the potential integration of this approach with modern technology.